THE NEUTRON MONITOR TIME SERIES STATISTICS ANALYSIS AND EARTHQUAKES PREDICTION - Kussainov, A. S.; Pya, N. Y. (Хабаршы. Физика сериясы, 2011)
We have considered several methods for time series analysis applied to the neutron monitor counting rate and earthquake data set to find a possible correlation between the neutron counting rate at Tien-Shan mountain station and simultaneously registered earthquakes in 2000 km range from the target city of Almaty, Kazakhstan. This correlation has a complex form defined by the spatially and temporally ordered set of events and used to estimate the probability of an earthquake based on the readings of the station’s detectors located 50 km up in the mountains from the city.